DETERMINATION OF THE OPTIMAL CONFIGURATION OF TRIPLE CHELATE COMPLEXES OF THE ESSENTIAL TRACE ELEMENT ZINC WITH VITAMIN C AND ESSENTIAL AMINO ACIDS - A. V. Blinov; M. A. Pirogov; A. A. Gvozdenko; Al. B. Golik; A. A. Yakovenko; A. A. Blinova (Современная наука и инновации, 2023)
Within the framework of this work, the optimal configuration of triple chelate complexes of the trace element zinc with vitamin C and essential amino acids was determined using computer quantum chemical modeling. The interaction of the zinc atom with amino acids through a carboxyl group and an amino group and with vitamin C through various pairs of hydroxyl groups was considered. It has been established that the formation of triple zinc complexes with vitamin C and essential amino acids is possible, which is confirmed by the high difference in the total energy of the triple complex and the amino acid (∆E = 2449.910 ± 1.345 kcal/mol), as well as the chemical hardness value η ≥ 0.076 eV, indicating the stability of molecular complexes. It has been established that the optimal configuration of triple chelate complexes of the essential trace element zinc with vitamin C and essential amino acids is the interaction of zinc with ascorbic acid with OH groups attached to C3 and C6 atoms and with amino acids through the carboxyl and amino groups.